Bangladeshi women’s experiences and vulnerabilities in Jordan’s garment sector - Nassif, Gabriella; Bhuiyan, Muhammad Mahbubul; Zahir, Md; Abdulrahim, Sawsan; Ringler, Claudia (International Food Policy Research Institute, 2023)
Jordan’s garment sector employs a large number of women migrants from South Asia who face various challenges and vulnerabilities in their work environment. The COVID-19 pandemic has further exacerbated some of these vulnerabilities, leading to income losses. However, little information is available about this migration corridor. This study implemented qualitative phone survey interviews with returnee women migrants in Bangladesh to identify interventions that the organizations, such as the International Labor Organization and other actors supporting women’s safe migration could undertake to reduce women’s vulnerabilities in migration. The study identified networks of discipline and power, the perception of appropriate behavior at work and beyond and racialization as key areas that mediate vulnerabilities of women. We recommend increasing awareness of conditions at Jordan’s garment sector as part of pre-departure training, which is supported by the main recruitment practice of garment workers through BOESL in the country. Awareness raising includes information on the role of the Al Hassan Workers’ Center as well as on the role of the embassy of Bangladesh in Jordan. A second recommendation is to translate contractual documents into Bengali so that women migrants can better understand work conditions, including salaries. The final recommendation focuses on the need to continue research on the uneven power dynamics in Jordan’s garment sector to support dismantling networks of discrimination and power and racialization of the work environment.